The Quiet Quitting Epidemic: Toxic Workplaces, Job Insecurity, and Gen Z’s Search for Grit - Azizah, Erza Agistara; Samian, Samian; Suhariadi, Fendy (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
The high prevalence of quiet quitting (QQ) among Generation Z (a global average of 59%, with the figure in Indonesia being even higher, reaching 67.84%) indicates a profound problem within the current work industry. Particularly in the high-pressure financial sector, Gen Z is suspected to be highly susceptible to toxic work environment (TWE) and job insecurity (JI) as triggers for QQ. Therefore, this study aims to explore the moderating effects of organizational career growth (OCG) and grit on QQ’s relationship with TWE and JI, based on the Conservation of Resources Theory and using a quantitative approach. The sample consisted of 107 Gen Z employees in the financial sector. Data analysis was performed using partial least squares structural equation modeling (PLS-SEM). The results demonstrate that TWE and JI have a positive and significant effect on QQ. OCG and grit significantly weaken the effect of TWE on QQ, but do not significantly moderate the effect of JI. These findings serve as a reference for organizations to anticipate QQ among Gen Z by providing clear career development paths, grit training programs, and a stable work environment through long-term contracts and open dialogue regarding company sustainability.